Improvement of osteoblast adhesion, viability, and mineralization by restoring the cell cytoskeleton after bisphosphonate discontinuation in vitro - Somying PATNTIRAPONG; Chunya CHAMPAKERDSAP; Pichaya MATHAVEECHOTIKUL; Apichaya VATANASILP (University of São Paulo, 2024)
Abstract Bisphosphonates are prescribed to treat excessive bone resorption in patients with osteoporosis. However, its use is associated with potential adverse effects such as medication-related osteonecrosis of the jaw, prompting the introduction of the drug holiday concept in patients prior to dentoalveolar surgery. Furthermore, bisphosphonate discontinuation has been studied in vivo, in humans, and in animal models. However, it is not known whether this approach could affect bone cells in vitro. Therefore, the objective of this study was to investigate the potential effects of bisphosphonate discontinuation on pre-osteoblast and osteoblast activities in vitro. Methodology Pre-osteoblasts (MC3T3) and osteoblasts were treated with bisphosphonate (alendronate) at concentrations of 1, 5, and 10 µM. Alendronate was then withdrawn at different time points. The negative control consisted of untreated cells (0 µM), while the positive control consisted of cells incubated with alendronate throughout the experiment. Cell viability, cell adhesion, cell cytoskeleton, mineralization, and gene expressions were investigated. Results Pre-osteoblasts and osteoblasts showed a decrease in cell viability after treatment with 5-10 μM alendronate for 4 days or longer. Two days of alendronate discontinuation significantly increased cell viability compared with the positive control. However, these levels did not reach those of the negative control. Bone nodule formation was reduced by alendronate. Discontinuation of alendronate regained bone nodule formation. Longer periods of discontinuation were more effective in restoring nodule formation than shorter periods. Addition of alendronate resulted in an increase in the percentage of dead cells, which, in turn, decreased when alendronate was discontinued. Alendronate affected the cell cytoskeleton by disassembling actin stress fibers. Cell adhesion and cell morphological parameters were also affected by alendronate. Discontinuation of alendronate restored cell adhesion and these parameters. Overall, the highest improvement after alendronate discontinuation was seen at 10 µM. However, alendronate treatment and discontinuation did not affect osteoblast gene expression. Conclusion Discontinuation of alendronate helps to reverse the negative effects of the drug on cell viability, cell adhesion, and mineralization by restoring the cell cytoskeleton. Our data suggest the benefits of drug holiday and/or intermittent strategies for alendronate administration at the cellular level.